Transport scheduling system in SUK Pahang using heuristic method - Desmond Chong Shin, Koh (2012)
Transport Scheduling System in SUK Pahang is a system design using Heuristic Method(HM).The system was built to enhance the schedule options by giving fair equalizer in using the resources such as drivers and transports.Personnel scheduling problems deal with the issue of assigning drivers and vehicles to shifts in a certain time period for the journey,such that several regulations are satisfied and preferences of the drivers and vehicles are taken into account,level of service is maximized [1].The scheduling system will be based on mathematical programming for optimization. As we know, HM has been variously presented in many kinds of form such as filtering,criteria,production rules,and procedure[3].In this scheduling system,filtering, procedures,and criteria which base on the constraints will be used using HM.